Solar Energy Management in Electricity Load Application of Household Room Based on IoT - Syarifah Akmal; Selamat Meliala; Yasir Amani; Saifuddin Muhammad Jalil (Journal of Renewable Energy, Electrical, and Computer Engineering, 2024)
Currently using electrical energy is very large and electrical energy security continues to be studied by government. Developments starts from using and managing of renewable energy sources. Energy sources will not be run out. One of which is using heat energy from sunlight. Using The use of the concept of renewable energy utilization strategy is still 17%. The energy management method is to use a smart system where if the room is during the day, the LDR sensor will signal to the microcontroller so that the room lights will turn off and if there is heat the DHT22 sensor detects the room temperature of 300 C. Then the fan turns on and cools the room so that it will cool down and the load that is not needed by the grid will not function so that energy consumption will be reduced according to calculated needs. This working system is based on IOT derived from ESP 8266 to store solar energy consumed by the house room. The smart method used in the research is to place 3 DHT22 sensors for optimal heat temperature. Average temperature sensor data, LDR data is stored in the data logger in the form of xls files on Gdrive. xls files then for 15 days. From the results of the date per 15 days on 13-11-2023, the design obtained an average temperature of 30.90 with a consumption of 5.83 kWH at a cost of 7882.16 rupiah.